Security Management Model for Mobile Databases Transaction Management - Ziyad. T., Abdul-Mehdi; Mahmod, Ramlan (2008)
Mobile database permeates into today's computing and communication area; we envision application infrastructures that will increasingly rely on mobile technology. Transaction's security of database will need to integrate peer-to-peer mobile environment: people and computers. In this paper we develop a security model for transaction management framework for peer-to-peer environments. A key requirement in such an environment is to support and secure frequent disconnection of mobile database. We present algorithms that implement this framework in an asynchronous and synchronous system.